At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Why can't you use the Zero-Product Property to solve (x-1)(x+3)=1?

Sagot :

If ( x - 1 ) * ( x + 3 ) = 0 => x = 1 or x = -3;
But, (x-1)(x+3)=1 => x^2 + 3x -x - 3 = 1 => x^2 + 2x - 4 = 0;the discriminant is 2^2 - 4 * 1 * ( -4 ) = 20 => the solutions are x1 = 
( - 2 + [tex] \sqrt{20} [/tex]) / 2 ; x2 = - 2 - [tex] \sqrt{20} [/tex] ) / 2;